Explosively driven hierarchical particle jetting. (20th July 2019) - Xue, Kun; Liu, Jiaqi; Feng, Chun; Gan, Yixiang; Bai, Chunhua
Graphical abstract: Highlights: Explosive driven particle jetting is modeled by a FEM-DEM coupling method. The origin of a distinctive hierarchical particle jetting pattern is identified. The meso-scale mechanisms underlying the jetting pattern are revealed. Microstructure of particle packings significantly affects the jetting patterns. Abstract: When particle rings/shells are subjected to divergent explosive loadings, a dual overlapping particle jetting structure emerges during the shock interaction timescale which consists of a large number of minor jets initiated from the external interface at very early instants and a much reduced number of major jets formed from the internal interface at delayed times but overtaking the minor jets in later times. In the present work, the formation of the hierarchical particle jetting pattern is investigated numerically by discrete element method (DEM) coupled with finite element method (FEM), which execute the mechanical calculations of particles and the explosive/detonation gases, respectively. The numerical results find that the external jetting arises from the spallation of an outer layer pulled away by inward propagating rarefaction waves. Meanwhile an inner compact band re-compressed by a secondary shock remains densely packed while expanding outward. The fragmentation of the inner compact particle band, preceding the internal particle jetting, is caused by the profuse spiral shear failures expanding from the inner radius to the outer radius. The resultant jetting structure depends on the shear-band spacing and the grouping of the clockwise and counterclockwise shear bands as well. The former is a function of the bulk characteristics of the inner compact band, especially the resistance to the shear flows. The latter markedly varies with the microstructure of particle packing, especially the structural order. In the highly ordered extreme, the particle ring with global crystalline structure exhibits six groups of shear bands, probably giving rise to around six fragments. By contrast, the grouping of shear bands in the amorphous packing is far from definite, suggesting an increased number of much smaller fragments to be generated. The dual jetting structure would degenerate into a single jetting pattern if the inner compact band manages to entrain all the spall particles before the shear failure occurs.